Factors Affecting Staff Retention Strategies Used in Private Syrian Companies during the Crisis - Gharib, Moaz Nagib; Kahwaji, Ahmad Taha; Elrasheed, Mohammed Osman (International Review of Management and Marketing, 2017)
The aim of current study is to exam elements influencing retention among employees in private Syrian companies during the crisis. The factors are training and professional development, organizational rewards system, job insecurity and job satisfaction. For this reason, 102 organized surveys were gathered. Obtained results from the study questionnaire were analyzed and examined by using statistical tests as Correlation and Multiple Regression analysis. Results show that training and professional development have no significant impact on staff retention, while other variables (Rewards system, Job security and Job satisfaction) have statistically significant effect on staff retention, analysis showed that Job satisfaction has more effect than rewards system and job security on staff retention. Keywords: Staff Retention, Training, rewards system, Job security, Job satisfaction, Crisis, Syria. JEL Classifications: J63, M12